2015
DOI: 10.1016/j.contraception.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Three-year efficacy and safety of a new 52-mg levonorgestrel-releasing intrauterine system

Abstract: A new 52-mg levonorgestrel-releasing intrauterine system is effective and safe for nulliparous and parous women for at least 3 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
89
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 21 publications
2
89
1
3
Order By: Relevance
“…The methods of the primary study have been reported previously [9]. Briefly, investigators at 29 clinical sites in the United States enrolled healthy, nonpregnant, sexually active, nulliparous and parous women aged 16-45 years (inclusive) who desired a hormonal IUS for contraception from December 2009 to April 2013.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods of the primary study have been reported previously [9]. Briefly, investigators at 29 clinical sites in the United States enrolled healthy, nonpregnant, sexually active, nulliparous and parous women aged 16-45 years (inclusive) who desired a hormonal IUS for contraception from December 2009 to April 2013.…”
Section: Methodsmentioning
confidence: 99%
“…This US study of women primarily using the LNG 52 mg IUS for contraception had significant proportions of obese and nulliparous women, which allowed for a broad, generalizable assessment of the characteristics of women who develop amenorrhea [9].…”
Section: Introductionmentioning
confidence: 99%
“…The methods of this study have been reported previously [3]. A central or local Institutional Review Board for each center approved the study.…”
Section: Methodsmentioning
confidence: 99%
“…A featured article in this print issue by David Eisenberg and colleagues [1] is the main report of the initial 3-year safety and efficacy results of the levonorgestrel intrauterine system, a new intrauterine system just approved by the U.S. Food and Drug Administration (FDA). This intrauterine system is deservedly much heralded in the U.S. where it will be available at a particularly low cost for public sector clinics (currently, 340B clinics), thus increasing access for many women.…”
Section: Introduction To Volume 92mentioning
confidence: 98%